Causas de abandono del tratamiento de diabétes mellitus tipo 2 de pacientes en medicina interna del hospital Isidro Ayora - Ocampo Ordóñez, Valeria del Cisne (2014)
The Mellitus Diabetes type 2 is the most common diabetes class. The familiar backgrounds, the lack of physical activity, a wrong diet, overweight and obesity are risk factors to acquire the disease. Within the medical treatment to cope with this disease are oral hypoglycemic agents and insulin in order to delay the complications in the patient as:: Diabetic foot, diabetic retinopathy, nephropathy, Cardiovascular Diseases, Chronic Kidney Disease. In this research study, denominates “CAUSES OF ABANDONMENT OF THE MELLITUS DIABETES TYPE 2 TREATMENT OF PATIENTS ATTEND IN INTERNAL MEDICINE OF THE ISIDRO AYORA HOSPITAL”, was a descriptive study, we aimed to identify the causes of discontinuation and its relationship to the complications of the disease motivated their income, for which 30 patients over 50 years admitted to the service because of this were surveyed. The results indicate that patients admitted to the internal medicine service during the period of the research, 63.33 % are female and 36.67 % male, the most affected age group was patients between 71 and 80 years age, single / as, with secondary level education, with income less than SUB and home. Among the socio-cultural factors related to complications of Diabetes Mellitus Type 2 of these patients in their order is : not fit to own diet for your condition 90 % , lack of exercise 73.33 % , breach of medical 56.66 % treatment , I forget 41.18 % have no one to give them medication 35.29 % ; and 30 % are single. Keywords: chronic illness, abandonment, treatment, factors, elderly women